AI chatbot distractions and academic triumphs: a mediation approach with self-control and coping skills - Prayoga, Hadiyan; Wakhid, Zukhruf Nur (Journal of Accounting and Investment, 2024)
Research aims: This study investigates self-control and coping skills in academic performance moderated by AI Chatbot addiction.Design/Methodology/Approach: This study used an online survey and archival method and included 153 accounting student respondents as the final sample. Structural Equation Modelling using Smart-PLS was employed to estimate the relationship between variables.Research findings: The findings underscore the significant impact of self-control in mitigating addictive tendencies, highlighting the susceptibility of individuals with lower self-control to develop addictive behaviors toward AI Chatbots. In comparison, coping skills were not found to have a substantial effect on reducing AI Chatbot addiction.Theoretical contribution/Originality: This research demonstrates that self-control and coping skills play a crucial role in controlling the dependence on AI-based chatbots, ultimately contributing to a better understanding of the relationship between these psychological abilities and managing AI addiction in university accounting students (Chassignol et al., 2018; Sollosy McInerney, 2022).Practitioner/Policy implication: The findings have implications for chatbot designers and developers. Understanding the potential for addictive behavior allows for the implementation of behavior detection and prevention mechanisms within chatbot designs.Research limitation/Implication: This study overlooked diverse forms of self-control and coping skills, along with other factors that contribute to AI Chatbot addiction. Recommending the exploration of various self-control strategies and coping skills could be a valuable opportunity for future research.